PEMANFAATAN APLIKASI RUMAH BELAJAR DALAM MENDUKUNG PROSES PEMBELAJARAN KELAS IV SDN 03 JABALSARI - Retno Septiani; Nugrananda Janattaka (Program Studi PGSD Universitas Flores, 2022)
The function of information and communication technology has created a new learning method in the world of education, namely web-based learning media as an innovative learning method, one of which is Rumah Belajar applications. This study aims to describe the use of Rumah Belajar applications in supporting the learning process. This study uses a descriptive qualitative research method with a phenomenological approach. This type of qualitative research with a phenomenological approach is expected to reveal the situation and problems faced. The stages in conducting this research are the pre-field stage, the implementation stage, the data analysis stage, and the evaluation or reporting stage. Collecting data in this study using observation, interviews, and documentation. The results of the study show that the Rumah Belajar application provides various features which are divided into main features and supporting features. Its main features include sumber belajar features, laboratorium maya features, bank soal features, and kelas digital features. Supporting features include a peta budaya feature, an buku sekolah elektronik feature, a wahana jelajah angkasa feature, a karya bahasa dan sastra feature, a pengembangan keprofesian berkelanjutan feature, a blog pena feature, an edugame feature, and an augmented reality feature that can be accessed and function by teachers and students in carry out learning activities.